The Women’s Language Features in Moana Movie - Sanjaya, Yosep (Humanis, 2018)
The title of this paper is The Women’s Language Features in Moana Movie. This study aimed at identifying the women’s language features are applied by women and finding the context of the situation that influenced women’s language. The women’s language is analyzed based on the theory of sociolinguistics which is proposed by Lakoff (1975). The second theory applied to analyze the context of the situation is proposed by Halliday and Hasan (1989) who divides into three concepts: field of discourse, tenor of discourse, and mode of discourse. The data of this study was taken from a movie entitled Moana . The movie was chosen as the data source in this study because it contained many women conversations either formal or informal situation. The analysis comes to a conclusion. There were seven features of women’s language found in the movie entitled Moana, and the context of situation that influenced women language.